Role of partner support in psychosexual aspects of vulvar dermatoses - Tolu Adedipe (Korean Society of Obstetrics and Gynecology, 2021)
Women with vulvar dermatoses report a psychosexual effect due to the chronicity of symptoms and long-term treatment as the disabling nature of the condition impacts their sexual relationship. Partner role and support in the management of psychosexual impact are poorly understood and are not part of the routine care for increasing number of women with vulvar dermatoses. This paper provides an aide-mémoire for identifying patient concerns and supporting the partner. Holistic care of the affected women comprises assessment and management of the psychosexual impact of the disease on them and their partners through a dyadic or paired perspective. Limitations regarding the impact of increased virtual consultations, secondary to the recent global pandemic, and issues related to gender identity with sexual orientation are recognized.